Photodeposition-Based Synthesis of TiO2@IrOx Core–Shell Catalyst for Proton Exchange Membrane Water Electrolysis with Low Iridium Loading - Hoffmeister, Darius; Finger, Selina; Fiedler, Lena; Ma, Tien Ching; Körner, Andreas; Zlatar, Matej; Fritsch, Birk; Bodnar, Kerstin Witte; Carl, Simon; Götz, Alexander; Zubiri, Benjamin Apeleo; Will, Johannes; et al. (Advanced Science, 2024)
The widespread application of green hydrogen production technologies requires cost reduction of crucial elements. To achieve this, a viable pathway to reduce the iridium loading in proton exchange membrane water electrolysis (PEMWE) is explored. Herein, a scalable synthesis method based on a photodeposition process for a TiO2@IrOx core–shell catalyst with a reduced iridium content as low as 40 wt.% is presented. Using this synthesis method, titania support particles homogeneously coated with a thin iridium oxide shell of only 2.1 ± 0.4 nm are obtained. The catalyst exhibits not only high ex situ activity, but also decent stability compared to commercially available catalysts. Furthermore, the unique core–shell structure provides a threefold increased electrical powder conductivity compared to structures without the shell. In addition, the low iridium content facilitates the fabrication of sufficiently thick catalyst layers at decreased iridium loadings mitigating the impact of crack formation in the catalyst layer during PEMWE operation. It is demonstrated that the novel TiO2@IrOx core–shell catalyst clearly outperforms the commercial reference in single-cell tests with an iridium loading below 0.3 mgIr cm−2 exhibiting a superior iridium-specific power density of 17.9 kW gIr−1 compared to 10.4 kW gIr−1 for the commercial reference.
CRIS-Team Scopus Importer:2024-06-21
Keywords: core–shell catalyst; iridium utilization; low loading; proton exchange membrane water electrolysis; thickness factor

The influence of intrinsically proton conductive electrode binder materials on HT-PEMFC performance - Arslan, Funda; Dirsch, Jens; Wagner, Maximilian; Freiberg, Anna; Komma, Miriam; Kerres, Jochen; Thiele, Simon; Böhm, Thomas (Journal of Power Sources, 2023)
High temperature proton exchange membrane fuel cells (HT-PEMFCs) typically employ either acid-absorbing or hydrophobic electrode binders in their catalyst layers (CLs). A recently introduced alternative is the ionomeric binder PWN, poly(2,3,5,6-tetrafluorostyrene-4-phosphonic acid). In literature, PWN with a phosphonation degree of 70% was shown to remarkably improve HT-PEMFC performance. Here, we investigate the influence of the phosphonation degree (40–95%) of this ionomeric binder on HT-PEMFC performance. PWN is employed in the cathode CL and compared to the commonly used polytetrafluoroethylene (PTFE) binder. The electrochemical behavior is tested at 180 °C at ambient pressure under H2/air conditions using a commercial phosphoric acid (PA)-doped PBI-membrane. HT-PEMFCs with PWN generally outperform fuel cells (FCs) with PTFE after a full break-in regarding peak power density (PPD), activation overpotential (as studied by Tafel analysis), and reproducibility in the mass transport region. Further, PWN-electrodes show higher electrochemically active surface areas (ECSAs) than PTFE-electrodes after completing the break-in. We find that the phosphonation degree has a substantial impact on the PPD, with PWNs with lower phosphonation degrees (40–60%) outperforming highly phosphonated PWNs (70–95%). Taken together, PWN as an ionomeric electrode binder in HT-PEMFCs shows remarkable improvements in performance, but a precise adjustment of the phosphonation degree is required to obtain optimal results.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Binder; Fuel cell; High temperature; Ionomer; Phosphoric acid; Proton exchange membrane; PWN